Transient receptor potential vanilloid-4 contributes to stretch-induced hypercontractility and time-dependent dysfunction in the aged heart - Veteto, Adam B (Cardiovasc Res, 2020)
AIMS: Cardiovascular disease remains the greatest cause of mortality in Americans over 65. The stretch-activated transient receptor potential vanilloid-4 (TRPV4) ion channel is expressed in cardiomyocytes of the aged heart. This investigation tests the hypothesis that TRPV4 alters Ca(2+) handling and cardiac function in response to increased ventricular preload and cardiomyocyte stretch. METHODS AND RESULTS: Left ventricular maximal pressure (P(Max)) was monitored in isolated working hearts of Aged (24–27 months) mice following preload elevation from 5 to 20mmHg, with and without TRPV4 antagonist HC067047 (HC, 1 µmol/L). In preload responsive hearts, P(Max) prior to and immediately following preload elevation (i.e. Frank–Starling response) was similar between Aged and Aged+HC. Within 1 min following preload elevation, Aged hearts demonstrated secondary P(Max) augmentation (Aged>Aged+HC) suggesting a role for stretch-activated TRPV4 in cardiac hypercontractility. However, after 20 min at 20 mmHg Aged exhibited depressed P(Max) (Aged<Aged+HC) suggestive of TRPV4-dependent contractile dysfunction with sustained stretch. To examine stretch-induced Ca(2+) homeostasis at the single-cell level, isolated cardiomyocytes were stretched 10–15% of slack length while measuring intracellular Ca(2+) with fura-2. Uniaxial longitudinal stretch increased intracellular Ca(2+) levels and triggered Ca(2+) overload and terminal cellular contracture in Aged, but not Aged+HC. Preload elevation in hearts of young/middle-age (3–12 months) mice produced an initial P(Max) increase (Frank–Starling response) without secondary P(Max) augmentation, and cardiomyocyte stretch did not affect intracellular Ca(2+) levels. Hearts of transgenic mice with cardiac-specific TRPV4 expression exhibited P(Max) similar to 3- to 12-month control mice prior to and immediately following preload elevation but displayed secondary P(Max) augmentation. Cardiomyocytes of mice with transgenic TRPV4 expression were highly sensitive to mechanical stimulation and exhibited elevated Ca(2+) levels, Ca(2+) overload, and terminal contracture upon cellular attachment and stretch. CONCLUSION: TRPV4 contributes to a stretch-induced increase in cardiomyocyte Ca(2+) and cardiac hypercontractility, yet sustained stretch leads to cardiomyocyte Ca(2+) overload and contractile dysfunction in the aged heart.